Novel monoclonal treatments in severe asthma. (26th November 2017) - Meteran, Howraman; Meteran, Hanieh; Porsbjerg, Celeste; Backer, Vibeke
ABSTRACT: Aim : To provide a general overview of the current biological treatments and discuss their potential anti-asthmatic effects. Data sources : We reviewed articles in PubMed found using the search words "Asthma/therapy AND antibodies, monoclonal/therapeutic use AND cytokines." Study selections : Only articles published in English since 2000 were considered. The search identified 29 studies; 8 additional studies were found by hand search, generating 37 studies. Results : Of the 37 studies investigating biological treatments of asthma, 5 were on the effects of anti-IgE (omalizumab); 12 on anti-IL-5; 8 on anti-IL-13; 5 on anti-IL-4R-α; 3 on anti-IL-9; one on TNF-α; one on anti-IL-2R-α; one on TSLP (Thymic Stromal Lymphopoietin); and one on OX40L. Sample sizes ranged from 3 to 943 participants. Studies of therapies targeting IgE, IL-2, IL4R-α, IL-5, and IL-13 showed some efficacy, whereas those targeting TSLP, IL-9, and TNF-α lacked convincing effectiveness. Conclusion : Research on the biological treatment of asthma shows promising results. While anti-IgE (omalizumab) has been used in the treatment of asthma for some years, anti-IL-5 has recently been approved for use. The efficacy of results of other large studies with a longer duration is needed to draw a firm conclusion. Such studies should not only focus on clinical outcomes, but also consider asthma-related quality of life. Knowledge on the asthma phenotypes and identification of biomarkers associated with these will be useful for physicians considering the right treatment for the asthma patient.